Increasing organic carbon biolability with depth in yedoma permafrost - Heslop, J. K.; Winkel, Matthias; Anthony, K. M. Walter; Spencer, R. G. M.; Podgorski, D. C.; Zito, P.; Kholodov, A.; Zhang, M.; Liebner, Susanne (Jun.-Prof. Dr.) (Journal of Geophysical Research: Biogeosciences, 2019)
Permafrost thaw subjects previously frozen organic carbon (OC) to microbial decomposition, generating the greenhouse gases (GHG) carbon dioxide (CO2) and methane (CH4) and fueling a positive climate feedback. Over one quarter of permafrost OC is stored in deep, ice-rich Pleistocene-aged yedoma permafrost deposits. We used a combination of anaerobic incubations, microbial sequencing, and ultrahigh-resolution mass spectrometry to show yedoma OC biolability increases with depth along a 12-m yedoma profile. In incubations at 3 degrees C and 13 degrees C, GHG production per unit OC at 12-versus 1.3-m depth was 4.6 and 20.5 times greater, respectively. Bacterial diversity decreased with depth and we detected methanogens at all our sampled depths, suggesting that in situ microbial communities are equipped to metabolize thawed OC into CH4. We concurrently observed an increase in the relative abundance of reduced, saturated OC compounds, which corresponded to high proportions of C mineralization and positively correlated with anaerobic GHG production potentials and higher proportions of OC being mineralized as CH4. Taking into account the higher global warming potential (GWP) of CH4 compared to CO2, thawed yedoma sediments in our study had 2 times higher GWP at 12-versus 9.0-m depth at 3 degrees C and 15 times higher GWP at 13 degrees C. Considering that yedoma is vulnerable to processes that thaw deep OC, our findings imply that it is important to account for this increasing GHG production and GWP with depth to better understand the disproportionate impact of yedoma on the magnitude of the permafrost carbon feedback.